Melirik Trading Saham di Tengah Pandemi dengan Teknik Moving Average Covergence Divergence (MACD) - Zulistiani Zulistiani (POLITEKNIK CAHAYA SURYA, 2020)
Stock trading aims to seek profit from the act of buying and selling shares in a flash, so a trader should have the ability to perform technical analysis before carrying out a stock sale and purchase transaction. This study aims to determine the decision to buy and sell shares using technical analysis Moving Average Covergence Divergence. (MACD). A quantitative approach with descriptive techniques is used in this study. The analysis technique of this research is the Moving Average Convergence Divergence (MACD) analysis. This study uses a population of shares in the telecommunications sector in Indonesia, namely shares of PT Smartfren Telecom Tbk (FREN), PT. Indosat Tbk (ISAT), PT. XL Axiata Tbk (EXCL), and PT. Telekomunikasi Indonesia (Persero) Tbk (TLKM). Researchers took daily stock price movement chart data from 15 December 2019 to 15 June 2020 through the PROFITS application. The conclusion of this study is that for the shareholders of the four companies, they should sell shares they own to maximize profits. Keywords: Trading , Saham, MACD